2001
DOI: 10.1007/s004670100697
|View full text |Cite
|
Sign up to set email alerts
|

Repeat renal biopsy in a girl with tubulointerstitial nephritis and uveitis syndrome

Abstract: A Japanese girl aged 8 years who presented with a 2-month history of uveitis subsequently developed tubulointerstitial nephritis. A percutaneous renal biopsy revealed massive interstitial mononuclear cell infiltrates consisting of CD4-positive T cells. Despite administration of topical corticosteroids, the ocular symptoms persisted. Systemic corticosteroid therapy dramatically reduced the ocular symptoms and urinary beta2-microglobulin (beta 2MG) concentration. However, reducing the prednisolone dosage induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…The renal prognosis has been considered to be favorable, although this was largely based on case reports or retrospective studies of a small number of patients (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The long-term outcome of TINU syndrome, especially in adults, has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The renal prognosis has been considered to be favorable, although this was largely based on case reports or retrospective studies of a small number of patients (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The long-term outcome of TINU syndrome, especially in adults, has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…14 In comparison with other renal diseases and normal controls, the high prevalence of serum anti-mCRP autoantibodies in TINU syndrome was impressive, especially in the active phase of nephritis. 14 Otherwise, some studies have described that renal tubulointerstitial infiltrates are primarily composed of activated lymphocytes, among which the helper/inducer T-cell subset is reported to be predominant, 22,23 furthermore, cell-mediated immunity, in particular delayed-type hypersensitivity, could play a large role in TINU syndrome. 24 Most of the studies describing immunohistochemical kidney analysis in TINU patients have demonstrated that interstitium is infiltrated mainly by T-cells together with monocytes/macrophages 25,26 and the case reports of Abed et al 22 and others have described that the helper/inducer T-cell subset was predominant in renal interstitial infiltration in TINU.…”
mentioning
confidence: 99%
“…Persistent renal dysfunction, ocular complications and chronic course may appear in some cases (5). Treatment is controversial but patients are usually treated with systemic corticosteroids and immunosuppressive drugs and the renal outcome in children is usually good but uveitis tends to follow a relapsing course (2,3).…”
mentioning
confidence: 99%